A Translation Analysis of Negative Polarity Idioms in The Hate U Give Novel - Azizah, Safitri Nur (Jurnal Bahasa, Sastra, dan Studi Amerika, 2023)
This research focuses in analysing negative polarity idioms found in the novel entitled The Hate U Give, the strategies used by the translator in translating the idioms, and the impacts of the strategies on the quality of the translation of negative polarity idioms in The Hate U Give novel in terms of accuracy and acceptability. There are 74 data of negative polarity idioms collected. The negative polarity idioms found are classified based on the negation expressed. This study indicates four strategies of translating idiom used by the translator of The Hate U Give novel. The strategies are: 1) using an idiom of similar meaning and form, 2) using an idiom of similar meaning but dissimilar form, 3) translation by paraphrase, and 4) translation by omission of a play on idiom. The results on the translation quality show that the translation is accurate and acceptable. The findings also reveal the impact of translation strategies on the quality of translation. The strategies which contribute to accurate translation are translation by using an idiom of similar meaning and form, using an idiom of similar meaning but dissimilar form, and translation by paraphrase. Meanwhile, for the acceptability aspect, all four strategies contribute to acceptable translation.